FINANCIAL REPORTING ANALYSIS TO MEASURE THE FINANCIAL PERFORMANCE OF THE LOCAL GOVERNMENT OF TOBA REGENCY - Purba, Sahala; Purba, Rani Agustines; Simangunsong, Lucyanna Yosephine; Gultom, Nadia A.V.E; Sinaga, Agnes Patricia R. (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
The purpose of this study is to examine the financial performance of local governments seen from 8 government financial ratios, the data is analyzed descriptively quantitatively with the subject of research on the financial statements of the Regional Government of Toba Regency for 2020-2022. The data collection technique carried out is a documentation technique. The results showed that the financial performance of the Toba Regency government as follows: (1) The Financial Independence Ratio, Regional Financial Dependence Ratio, and Fiscal Decentralization Degree Ratio showed very low results with average values of 7.80%, 6.62%, and 6.62%. (2) The PAD Effectiveness Ratio and Regional Tax Effectiveness Ratio showed very effective results with average values of 104.33% and 111.68%. (3) The PAD Efficiency Ratio and Regional Tax Efficiency Ratio showed very efficient results with high average values of 98.47% and 1.13%. (4) The ratio of BUMD Contribution Degrees shows quite high results with an average value of 11.10%. Based on the results of the analysis, it can be said that Toba Regency has not been good enough in financial implementation and management.